Structure-Activity Relationships of Glucose-Dependent Insulinotropic Polypeptide (GIP) - Hinke, S.A.; Gelling, R.; Manhart, S.; Lynn, F.; Pederson, R.A.; Kühn-Wache, K.; Rosche, F.; Demuth, H.-U.; Coy, D.; McIntosh, C.H.S. (Biological chemistry, 2003)
Six GIP1-30NH2 analogs were synthesized with modifications (de-protonation, N-methylation, reversed chirality, and substitution) at positions 1, 3, and 4 of the N-terminus, and additionally, a cyclized GIP derivative was synthesized. The relationship between altered structure to biological activity was assessed by measuring receptor binding affinity and ability to stimulate adenylyl cyclase in CHO-K1 cells transfected with the wild-type GIP receptor (wtGIPR). These structureactivity relationship studies demonstrate the importance of the GIP N-terminus and highlight structural constraints that can be introduced in GIP analogs. These analogs may be useful starting points for design of peptides with enhanced in vivo bioactivity.